An Analysis of Employee's Work Motivation at TK. IV 02.07.01 Zainul Arifin Hospital in Bengkulu City - Lorita, Evi; Amin C. Kader, Bando; Hairani, Risadyla; Sariningsih, Marida (Indonesian Association for Public Administration (IAPA), 2023)
This study aims to determine the work motivation of employees at TK IV 02.07.01 Zainul Arifin Hospital in Bengkulu City. This study used descriptive qualitative method. Data collection used interview and documentation techniques by using the Classical Theory of Motivation Hierarchy of Needs by Abraham Maslow (1943). There were five assessment indicators used, namely: (1) Physiological, (2) Sense of Security, (3) Social, (4) Awards, and (5) Self-Actualization. The results of the study showed that employees at the hospital works with high motivation, fulfills rights in the form of salary and work holidays, provides employees' needs both at work and personal needs, creates a sense of security with existing protection, awards are given for every job done, availability training aimed at employees for self-development and additional knowledge of employees. Social relations between the employees and self- actualization are good enough, but there are still employees who are not able to socialize at work.